Examining Posttraumatic Growth After a Natural Disaster: An Appreciative Inquiry Approach - Alyssa Powell; Kevan W. Lamm (Journal of International Agricultural and Extension Education, 2021)
With the frequency and intensity of natural disasters expected to increase as climate change persists, it is crucial for agricultural educators and extension agents around the world to develop the capacity to assist individuals in the wake of traumatic natural disasters. Data were collected in January 2019 and surveyed Georgiaresidents who theythemselves, or someone they cared about, were affected by Hurricane Michaelwhich occurred in October 2018. Data were measured using a modified version of Tedeschi and Calhoun’s (1996) 21-item posttraumatic growth inventory. Highest mean posttraumatic growth scorewasassociated with the Relate to Others scale, while the lowest mean score was associated with the Appreciation of Life scale. Approximately 48% of respondents reported a large or very large change in their compassion for others and their appreciation of each day as a result of their traumatic experience. Female respondents scored higher than male respondents on all the posttraumatic growth factors. Significant differences at the .05 level between male and female mean posttraumatic growth scores were identified for five scale factors;personal strength; spiritual change; appreciation of life; and overall posttraumatic growth. These findingssuggest females may bemore adaptive to traumatic events and more likely to be receptiveto the potential to perceivepositive benefits resulting from traumatic experiences. An associated recommendation would be for agricultural educators and extension personnel to utilize the appreciative inquiry approach when assisting individuals recovering from natural disasters and other traumatic events.
Keywords: posttraumatic growth; Hurricane Michael; natural disasters; appreciative inquiry